A Cross-sectional Study on the Levels of Anxiety and Depression of People under Treatment for COVID-19 in Relation to Emotional Intelligence - Gopi Rajendhiran; V. Veera Balaji Kumar (Indian Journal of Psychiatric Nursing)
Background: COVID-19 was one of the pandemics which had put human emotional tolerance into hazard and tested our endurance levels. Emotional intelligence (EI) is described as the ability to identify, understand, and use emotions positively to manage anxiety, communicate well, empathize, overcome issues, solve problems, and manage conflicts. This study aims to understand the level of anxiety, depression, and EI of people who are recovering from COVID-19 in the hospital. Methods: A total of 295 people out of 480 COVID-19 patients treated in a COVID-19 care center in Madurai participated in this study and a cross-sectional method of study was performed. Sociodemographic data and the levels of anxiety, depression, and EI were examined and Pearson’s correlation analysis was performed to identify the relationship between EI with the level of anxiety and depression. Results: The results indicate that people had 43.73% of the participants had mild levels of anxiety, 50.17% had moderate levels of anxiety, and 6.10% had severe levels of anxiety. Almost 50% of the participants had mild-to-moderate depression with regard to their current clinical condition irrespective of their levels of EI. However, there is a significant negative correlation between scores of EI and the levels of anxiety at α = −0.380, significant at P < 0.01. Conclusions: The results in this study have shown that EI is negatively correlated to the levels of anxiety in the participants. It shows that people high in EI are able to handle the sense of isolation and uncertainty in an effective manner.